An Analysis of the Social Networks in Health Promoting Schools - Kaeodumkoeng, Kwanmuang; Wongwanich, Suwimon; Pasiphol, Shotiga (Scholar: Human Sciences, 2015)
This multi-case study aims to compare the social networks of health promoting schools with different qualities of health service management. Selected using a purposive sampling technique, the samples were three secondary schools in Nonthaburi Province under the Office of the Basic Education Commission. The criteria for the selection were school size and the quality of health service management. From the three sample schools, 181 informants participated in the study. Data analysis included descriptive statistics, social network analyses using UCINET and Net Draw programs. The results were as follows. The social networks in health promoting schools with better health service management were larger and less centralized. Analyses of the whole-networks revealed that schools with different qualities of health service management had different social network characteristics. By the comparison of social networks of schools, it was found that network size and centralization can be used to categorize schools with diverse good health service management. The density of the network and eigenvector centrality cannot be clearly categorized.